Genotype by Environment Interactions in Barley (Hordeum vulgare L.) Cultivars for Nutritional Quality Assessment - Quddos, Abdul; Nadeem, Muhammad; Ahsan, Samreen; Khaliq, Adnan; Chughtai, Muhammad Farhan Jahangir; Rebezov, Maksim; Terent’ev, Sergei; Tryabas, Yulia; Ermolaev, Vladimir; Iskakova, Galiya; Konovalov, Sergey; Gayvas, Alexei; Shariati, Mohammad Ali (AGRIVITA, Journal of Agricultural Science, 2021)
In current study twenty-five barley genotypes were grown under RCBD (randomized complete block design). Barley flour was analyzed for proximate composition, β-glucan content, soluble and insoluble dietary fiber. Based on the results of nutritional quality best line (4158) was selected for the preparation of wheat flour supplemented bread. The sensory evaluation of bread was carried out to assess its suitability for consumers. The data obtained from all the experiments was subjected to statistical analysis by CRD. The results indicated that the highest moisture content (13.47%), protein content (13.93%), fat content (3.39%), fiber content (7.08%), ash content (2.67%) and NFE (71.54%) were observed in lines 4220, 4158, 4149, 4193, 4233, 4220 respectively. Similarly, significant differences for β-glucan (4.99%), total dietary fiber (16.62%), soluble (6.23%) and insoluble dietary fiber contents (10.36%) were observed in barley line 4193, 4233, 4168 and 4233, respectively. The bread prepared with the addition of 5% flour to wheat flour was liked most by the judges after the control bread. The current study showed significant potential of flour to be used by baking industry for the preparation of bread and other food products by the addition of flour.